A meta-analysis of effectiveness of teacher and peer feedback: Implications for writing instructions and research - Suthathip Thirakunkovit (2020)
© 2019 Asian E F L Journal Press. All Rights Reserved. This meta-analysis investigates the effectiveness of teacher and peer feedback. Over 5,000 articles from 41 journals in the fields of composition studies and second language writing and four electronic databases were identified. After careful screening and applying inclusion and exclusion criteria, only 27 primary studies, yielding 52 effect sizes, were analyzed. The results indicate a Hedges’ g effect size of .79 for the effectiveness of writing feedback in general. Feedback from teachers produces a larger effect size (Hedges’ g = .90), compared with peer feedback (Hedges’ g = .68). However, after examining the studies on peer feedback more closely, the researchers have found that there is a noticeable difference in effect sizes between peer feedback without training (Hedges’ g = .60) and peer feedback with prior training (Hedges’ g = .74). If specific instructions are given to students during peer training, it could result in higher improvement in the quality of student writing. Therefore, based on the results, the researchers would like to argue that not all peer feedback leads to significant performance improvement. The teachers have to provide specific training during the peer review process in order to enhance the quality and effectiveness of peer feedback. In this regard, peer feedback can have a strong positive effect on improving the quality of student writing.